Ethics, an Article in the Law or Individual Behaviour? An Overview of the Legal Framework in Albania on the Prevention of Conflicts of Interest during the Exercise of the Public Sector Functions - Miti (Ujkani), Mirela; Bërdica, Fatmir (Theoretical and Practical Research in Economic Fields, 2026)
At the core of current discourse on good governance and institutional integrity rests the complex interplay between ethics as a legal norm and ethics as individual behavior. It is precisely this dual nature of ethics, sometimes expressed as an article in the law and sometimes as a moral guide in preventing conflicts of interest during the exercise of public functions, that constitutes the central focus of this paper. Through a qualitative analysis of the Albanian legal framework and institutional practice, the paper examines the effectiveness of existing provisions in identifying and preventing situations involving conflicts of interest. The scientific contribution of this paper lies in highlighting the gap between the formal legal regulation of ethics and conflict of interest and their practical implementation, showing that legal provisions alone are insufficient to ensure effective prevention. Although legislation attempts to codify ethical standards through clear rules, the analysis demonstrates that sustainable prevention is intrinsically linked to individual awareness, institutional culture, and the ethical conduct of public sector employees. The paper argues that effective prevention requires a combined approach, integrating legal instruments with internal ethical responsibility, continuous education, and institutional commitment. In conclusion, the study emphasizes that while the existence of a legal framework is a necessary condition for safeguarding public integrity, it is not sufficient on its own. The prevention of conflicts of interest ultimately depends on a consistent and enduring interaction between legal provisions and an ethical culture internalized by individuals entrusted with public responsibilities.